Expanding the indications of pancreas transplantation alone - Mehrabi, Arianeb; Golriz, Mohammad; Adili-Aghdam, Fatemeh; Hafezi, Mohammadreza; Ashrafi, Maryam; Morath, Christian; Zeier, Martin; Hackert, Thilo; Schemmer, Peter (Pancreas, 2014)
OBJECTIVES: Total pancreatectomy (TP) is associated with postoperative endocrine and exocrine insufficiency. Especially, insulin therapy reduces quality of life and may lead to long-term complications. We review the literature with regard to the potential option of pancreas transplantation alone (PTA) after TP in patients with chronic pancreatitis or benign tumors. - METHODS: A MEDLINE search (1958-2013) using the terminologies pancreas transplantation, pancreas transplantation alone, total pancreatectomy, morbidity, mortality, insulin therapy, and quality of life was performed. In addition, the current book and congress publications were reviewed. - RESULTS: Total pancreatectomy after benign and borderline tumors as well as chronic pancreatitis is continuously increasing. Despite improvement of exogenous insulin therapy, more than 50% of these patients experience severe glucose control problems, which cause up to 50% long-term mortality. Pancreas transplantation alone can cure both endocrine and exocrine insufficiency and reduce the associated risks. The 3-year graft and patient survival rates after PTA are up to 73% and 100%, respectively. - CONCLUSIONS: Pancreas transplantation alone after TP in patients with pancreatitis or benign tumors improves the recipient's quality of life and reduces long-term mortality. Considering the amount of available organs and potential candidates, PTA can be a treatment option for patients after TP with chronic pancreatitis or benign tumors.